Mediating Effect of Depressive Symptoms in the Relationship Between Cardiovascular Risk Factors and Health Conservation in Community-Dwelling Vulnerable Diabetic Elderly People - Sung, Kiwol (Journal of Hypertension and Cardiology, 2016)
Purpose: The purpose of this study was to examine the mediation of depressive symptoms in the relationship between cardiovascular risk and the health conservation of community-dwelling vulnerable diabetic elderly in order to provide a basis for planning nursing interventions to improve the health conservation of vulnerable diabetic elderly. Methods: The participants were 99 vulnerable diabetic elderly who registered at the community health centers in D city. Data were collected using self-report questionnaires and analyzed with the SPSS-WIN 19.0 program. The instruments were Sung’s Health Conservation Scale, the Arizona Heart Institute Cardiovascular Risk Factor Questionnaire, and the Geriatric Depression Scale Short Form-Korea version (GDSSF-K). Results: The mean score for health conservation was 100.52. Overall depressive symptoms were 11.84, cardiovascular risk was 20.35. There were significant correlations among the three variables: health conservation, depressive symptoms, and cardiovascular risk. Also, depressive symptoms had a proportional mediating effect in the relationship between cardiovascular risk and health conservation. Conclusion: Based on the findings of this study, health management programs focusing on cardiovascular risk management and depressive symptom improvement are highly recommended to promote health conservation in the vulnerable diabetic elderly
Keywords: Keywords: conservation; cardiovascular; depression; vulnerable; aged